History of Tsutsugamushi Disease in Korea - Chung, Moon-Hyun (Infect Chemother, 2019)
Tsutsugamushi disease or scrub typhus in Korea was first officially reported in foreign soldiers in 1951 and in indigenous persons in 1986. However, the history is further prolonged. The book Dong Ui Bo Gam, published in 1613, described “Soo Dok” (water poisoning), which is similar to tsutsugamushi disease. Further, the term was mentioned in the book Hyang Yak Gu Geup Bang, first published in 1232–1251. During the Japanese colonial rule (1910-1945), Trombicula akamushi was identified in Suwon, Korea, in 1917. Although cases of tsutsugamushi disease in Korea with a murine typhus-like illness and OXK-positivity were reported in 1935, such atypical presentation was not recognized as tsutsugamushi disease. During the Korean War, in 1951, tsutsugamushi disease developed in two British soldiers stationed in the Imjin River, who presented typical features and positive OXK reactions. Indigenous cases have re-emerged since 1986. Thereafter, there were many studies on various aspects of tsutsugamushi disease: epidemiology, vector, small mammals, clinical features and complications, diagnosis, and treatment. Persistence of Orientia tsutsugamushi and its possible recrudescence with pneumonia were reported in 2012 and 2014, respectively.